Si Raja Smile” dalam meningkatkan kedisiplinan pendidik dan tenaga kependidikan di SMP Negeri 4 Depok - Hudaya Hudaya (Badan Penerbit STIEPARI Press, 2022)
The principal is a leader as well as an influential manager in determining the gates of success and progress in all areas of life in the school environment. He has a dominant role in improving the quality of learning outcomes and the success of the school he leads so that the principal is obliged to foster, examine, measure the work of educators in the school he leads including to organize and manage personnel, advice and funds. Every school member must know the meaning and benefits of discipline. The will to carry out discipline must come from oneself and without coercion from others. However, if the school community does not yet have awareness in this matter, it is necessary to impose coercion or obligations from the principal who is responsible for implementing and maintaining the disciplined attitude of educators and education staff. This Best Practice provides information about whether Si Raja Smile's strategy can improve the discipline and responsibility of educators and education staff at SMP Negeri 4 Depok? and How is the implementation of Si Raja Smile's strategy in increasing the discipline and responsibility of educators and education staff at SMP Negeri 4 Depok? The results depicted in this best practice occur when Si Raja Smile is implemented around 83%, can increase educator participation in flag ceremonies and tend to increase attendance by 87%. The number of educators in the educator's room during the flag ceremony decreased by 60%, and absenteeism decreased by 50%. This means that Si Raja Smile is very effective in increasing teacher attendance at the flag ceremony. And in the second evaluation, it increased to 95% the number of educators who were in the field was 47 people, in the educator's room 1 person (sick) and the number of educators who were not present because of illness.